Influence of the Extractant on the Complexing Capacity of Humic Substances from Peat for Macro and Micronutrients Using Continuous Flow: Agricultural Application and Environmental Impacts - Botero, Wander G.; Oliveira, Luciana C.; Cavagis, Alexandre D. M.; Rosa, André Henrique [UNESP]; Rocha, Julio Cesar [UNESP]; Santos, Ademir dos [UNESP] (Soc Brasileira Quimica, 2013)
The aim of the present work was to optimize a procedure for extraction of humic substances (HS) from peat, using continuous flow with different extractants (NaOH, KOH and Na4P2O7). The influence of extractant on the complexing capacity of humic substances for macro and micronutrients was also investigated. Our results showed that the extraction by flow is efficient, reducing the time required in the extraction step and, furthermore, indicating that the extracted HS have a high affinity for the essential nutrients Ca and Mg. Moreover, an enhanced complexation was achieved by using Na4P2O7, demonstrating not only the efficiency of this compound as extractant, but also its promising application in the process, since its high complexing capacity allows to make available the complexed nutrients as well as diminishing the amount of these nutrients that could be lixiviated, thus contributing to prevent environmental contaminations.
Keywords: humic substances; peat; complexation capacity; continuous flow extraction